Guide To The Department Of Oriental Manuscripts And Printed Books - Goodacre, H. J.; Pritchard, A.P. (London British Museum Publication Ltd., 1977)
Manuscripts, Oriental-Library resources
Asia -- Imprints -- Library resources.